PENGARUH MODEL MAKE A MATCH BERBANTUAN MEDIA STRIP STORY TERHADAP PEMAHAMAN KONSEP IPS KELAS V SDN 18 CAKRANEGARA - Fanida Wardani; Husniati; Asri Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the make a match model assisted by strip story media on the understanding of social studies concepts for class V SDN 18 Cakranegara. This type of research is an experiment with a Quasi Experimental design with the Nonequivalent Control Group Design type. The population of this study was 43 students using a saturated sampling technique consisting of 20 students in class V-A as the control class and 23 students in V-B as the experimental class. The data collection technique in this study used a test technique, namely a concept understanding test question instrument and a non-test technique in this study used a learning implementation observation sheet instrument. The data analysis technique in this research uses prerequisite tests, namely the normality test and homogeneity test. The normality test results for the experimental and control classes were found to be normally distributed and the homogeneity test results were Sig. is 0.303, which means > 0.05, so the data is declared homogeneous. The results of hypothesis testing were obtained through the independent sample t test to obtain a Sig value. (2-tailed) 0.022 < 0.05 and the value of tcount ≥ ttable is 2.381 ≥ 2.019, which means that Ha is accepted, Ho is rejected and the N-Gain test result is 0.5464, so it can be concluded that there is an influence of using the make a match model with the help of strip story media on understanding social studies concepts in class V at SDN 18 Cakranegara with a large influence of 0.5464 which is included in the medium category.